Real‐world evidence for subcutaneous infliximab (CT‐P13 SC) treatment in patients with psoriatic arthritis during the coronavirus disease (COVID‐19) pandemic: A case series. Issue 1 (20th January 2022) - Baraliakos, Xenofon; Tsiami, Styliani; Vijayan, Sooraj; Jung, Haewon; Barkham, Nick
Abstract: The COVID‐19 pandemic highlighted the benefits of subcutaneous (SC) administration for healthcare systems. The first SC infliximab, CT‐P13 SC, was safe and effective for the treatment of psoriatic arthritis. Observed patient preferences for continuing CT‐P13 SC suggest that patients receiving IV infliximab should be offered a switch to CT‐P13 SC.